2016
DOI: 10.1016/s1569-9056(16)15116-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of neck circumference in Benign Prostatic Hyperplasia in patients with metabolic syndrome

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Objectives: To investigate the impact of neck circumference (NC) in the treatment of bening prostatic hyperplasia (BPH) patients with metabolic syndrome (MtS). Additionally, we determined dose response to alpha-blockers and cut-off values for NC and waist circumference (WC), in these patients. Materials and Methods: Non-randomized, open-labelled, and multi-centre study was conducted between March 2014 and Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
1
5
0
1
Order By: Relevance
“…In the final statistical analysis, there were 18 studies reported the PSA level [16,17,19,20,[22][23][24][25][26][27][28][30][31][32][33][34][35][36]. There was no statistical difference in PSA level between the presence of MetS and the absence of MetS (WMD ¼ 0.04; 95% Cl: À0.06 to 0.13; p ¼ .43; Figure 3).…”
Section: Prostate-specific Antigenmentioning
confidence: 99%
See 3 more Smart Citations
“…In the final statistical analysis, there were 18 studies reported the PSA level [16,17,19,20,[22][23][24][25][26][27][28][30][31][32][33][34][35][36]. There was no statistical difference in PSA level between the presence of MetS and the absence of MetS (WMD ¼ 0.04; 95% Cl: À0.06 to 0.13; p ¼ .43; Figure 3).…”
Section: Prostate-specific Antigenmentioning
confidence: 99%
“…The data of Qmax was gained in 8 studies [23,27,28,[30][31][32]35,36]. The Qmax of the MetS group was lower than the non-MetS group (WMD ¼ À0.48; 95% Cl: À0.77 to À0.19; p ¼ .001; Figure 4(a)).…”
Section: Maximum Urinary Flow Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Эти особенности патогенеза ДГПЖ у больных с МС предполагают коррекцию терапии этих больных, особенно с учетом данных литературы о более низкой эффективности хирургического и медикаментозного лечения больных с ДГПЖ и МС по сравнению с паци-ентами без метаболических расстройств [70][71][72]. …”
Section: заключениеunclassified